Asymptomatic spontaneous cervical and mediastinal emphysema. (3rd July 2012) - Ojima, Hitoshi; Fukai, Yasuyuki; Soda, Makoto; Kuwano, Hiroyuki
Abstract : We report our experience with four patients presenting with spontaneous pneumomediastinum (SPM) within a 3-month period. The patients (three male and one female, aged 15–17 years) were hospitalised with SPM. All patients were kept under observation, successfully treated and followed up for several years, with no recurrences reported. Two patients had histories of asthma, while the other two developed SPM during sporting activities. SPM carries the possibility of being latent. For symptoms such as chest pain without evidence of pneumothorax in young people, it is necessary to always consider SPM and make the diagnosis accordingly.